Analisis Hubungan Daya Saing Sektor Basis dan Ketimpangan Pembangunan terhadap Pertumbuhan Ekonomi di Provinsi Jambi - Abdurrahman Abdurrahman; Zulgani Zulgani; Siti Hodijah (J-MAS (Jurnal Manajemen dan Sains), 2023)
This research aims to determine and analyze the relationship between competitiveness in basic sectors and economic development inequality on economic growth in Jambi Province. The method used in this research is a qualitative and quantitative descriptive method using secondary data during the 2000-2021 period. Data analysis in this study used the RCA method and Granger causality. The research results show that the industrial sector and mining sector have a causal relationship with economic growth in Jambi Province, while other sectors do not.